Nurse scholars' knowledge and use of electronic theses and dissertations - Goodfellow, L.; Macduff, C.; Leslie, Gavin; Copeland, S.; Nolfi, D.; Blackwood, Diana (Wiley-Blackwell Publishing Ltd, 2012)
Background: Electronic theses and dissertations (ETDs) are a valuable resource for nurse scholars worldwide. ETDs and digital libraries offer the potential to radically change the nature and scope of the way in which doctoral research results are presented, disseminated and used. An exploratory study was undertaken to better understand ETD usage and to address areas where there is a need and an opportunity for educational enhancement. Aims: The primary objective was to gain an initial understanding of the knowledge and use of ETDs and digital libraries by faculty, graduate students and alumni of graduate programs at schools of nursing. Design: A descriptive online survey design was used. Methods: Purposeful sampling of specific schools of nursing was used to identify institutional participants in Australia, New Zealand, the UK and the US. A total of 209 participants completed the online questionnaire. Results: Only 44% of participants reported knowing how to access ETDs in their institutions’ digital libraries and only 18% reported knowing how to do so through a national or international digital library. Only 27% had cited an ETD in a publication. The underuse of ETDs was found to be attributable to specific issues rather than general reluctance to use online resources. Conclusions: This is the first international study that has explored awareness and use of ETDs, and ETD digital libraries, with a focus on nursing and has set the stage for future research and development in this field. Results show that most nursing scholars do not use ETDs to their fullest potential.